BARIS KLEMAT DANCE IN MENEGA TEMPLE, SESEH TRADITIONAL VILLAGE, BADUNG, BALI - Dewi, Ni Putu Putri Laksmi; Ardini, Ni Wayan; Yudarta, I Gede (Institut Seni Indonesia Denpasar, 2025)
This research aims to reveal the origin and form of Baris Klemat dance in Bali as an integral part of sacred art and religious tradition. Baris Klemat dance is one of the sacred dances in Bali that has spiritual value and is closely related to the life of coastal communities. The research used a descriptive qualitative approach with data collection techniques through participant observation and in-depth interviews with traditional leaders, choreographers, composers, and people directly involved. The results showed that the Baris Klemat dance originated from the life of Balinese coastal communities, especially fishermen, as a form of expression of gratitude for the sea catch and protection from the sea gods. This dance is performed through dynamic movements and traditional tools such as klemat, kancuh, and pancer, representing fishermen's daily lives and strengthening their spiritual values. This dance plays an important role as a cultural ritual that reflects the identity of Balinese coastal communities and is part of a belief system passed down from generation to generation. This research makes an important contribution to strengthening the understanding of the cultural and spiritual richness of Baris Klemat dance. In addition, the results of this research are expected to encourage cultural sustainability and preservation of the identity of Balinese coastal communities so that the Baris Klemat dance remains alive and thriving as a valuable cultural heritage for future generations.